Improving Savings and Health by Maintaining Your Home at a Ready-to-Sell Level - Randall A. Cantrell (EDIS)
We never know when the market will allow for bidding wars on the price of homes, which was the case in some areas before the recent housing crisis. Similarly, we never know when we will have to make a decision about whether or not to move our family. This 4-page fact sheet reviews ways to maintain your home at a ready-to-sell level, which can be a benefit if you have to sell your home or relocate your family. Written by Randall A. Cantrell and published by the UF Department of Family, Youth and Community Sciences, March 2012.